Reconnaissances - Needham, Rodney (Heritage., 1980)
The reconnaissances of this book are ventures in the deep analysis of the unconscious as testified to by world ethnography. The topics examined are the image of the half-man, the operation of analogical classification, and ideas about sovereign powers to which men conceive themselves as subject.